Perioperative Radiotherapy in the Management of Rectal Cancer - Lars Påhlman (Canadian Journal of Gastroenterology)
Surgery for rectal cancer has resulted in unacceptably high local failure rates, and substantial morbidity and mortality. In an attempt to reduce the high frequency of local recurrence, perioperative radiotherapy has been used extensively, alone or in combination with chemotherapy. The local recurrence rate has been reduced dramatically with the use of radiotherapy, and provided that the dose is high enough and given preoperatively, the reduction rate has been about 50%. Despite that a higher dose is used in postoperative radiotherapy, the reduced recurrence rate is not that prominent. The reduced recurrence rate demonstrated after preoperative radiotherapy has a positive influence on survival, which has not been seen when radiotherapy is given postoperatively. However, when postoperative irradiation has been combined with chemotherapy, a survival benefit has been demonstrated. With modern radiation techniques, preoperative radiotherapy can be delivered without any substantial increase in postoperative mortality or morbidity, and a low rate of late toxicity, provided that the radiation technique is optimal. The main question is whether radiotherapy is necessary, provided that surgery is optimized. With standard surgery, the average local recurrence rate is 29% in all reported controlled trials. With optimal surgery, from institutional series, this figure is about 10%. Other questions to be answered are whether superfractionated or standard fractionation should be used in radiotherapy and exactly to whom it should be given.